Coastal Clean Up dalam Upaya Meningkatkan Kesadaran Masyarakat untuk Menjaga Lingkungan di Wilayah Pesisir Desa Sangrawayang, Sukabumi - Pipin Supinah; Amanda Chandra Safira; Ronny Wahju (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Kabupaten Sukabumi is one of the regencies in West Java which is directly bordered by the Indian Ocean in the south. Simpenan District, especially Sangrawayang village has many natural attractions, one of which is Loji beach. The existence of tourism triggers a lot of garbage, especially plastic. The Coastal cleanup program is expected to be a means to provide education to surrounding communities to maintain the cleanliness of the environment, especially the coastal environment. This program consists of two programs, namely beach cleaning and waste identification. The waste identification program was carried out on July 2 and July 8, 2019, in Cibutun Hamlet. The waste identification activity was carried out in 2 replications and spread in 10 stations. The results of identification on the first and second tests show that the sequence of waste from the highest to lowest amounts are wood, plastic, fabric, rubber, glass, and metal. Keywords: beach, coastal cleanup, garbage